Hem Realities: Augmenting Urbanism Through Tacit and Immersive Feedback. Issue 3 (2nd September 2019) - Wilkins, Gretchen; Stiff, Andrew
Abstract: This paper investigates a gap in the relationship between the physical city and current "smart city" solutions in the context of rapidly developing urban regions. In particular it reconsiders these two "realities": the material, spatial and social qualities of cities, and the immersive qualities of hybrid digital interfaces such as augmented and virtual reality. With regard to both analog and digital realms, our research proposes an inclusive and participatory approach to the design and implementation of smart city technologies. Using Ho Chi Minh City (or HCMC) as a case study, it explores how a city's tacit feedback, combined with mixed reality tools, can expand public accessibility of cities, and in particular of high-density districts. Activating the city through its citizens rather than relying on top-down political policies, this form of "augmented urbanism" advocates a community-based approach to transcending the smartness divide. Ho Chi Minh City offers many examples of shared, multifunctional spaces with localized forms of use and administration. However, these are under threat from intense urban development and subsequent environmental impact. This paper will suggest ways in which mixed reality tools could strengthen community engagement in neighborhoods that are marginalized or threatened by ongoing development, and how this process might also inform and bolster governmental support for locally-based initiatives. The research argues for the city itself (material and empirical) to identify, harness and leverage its own inherent forms of "smartness". Integrating the city's tacit knowledge with open-source platforms can ensure that the ongoing transformation of the city is a collective and intelligent one. This is also a way to provide persistent experiences within a radically and rapidly shifting urban environment.